PRODUKTIVITAS ALAT GALI MUAT DAN ANGKUT PADA KEGIATAN OVERBURDEN REMOVAL DAN COAL GETTING - Putrawiyanta, I Putu; Nadeak, Romualdo; Nababan, Immanuel (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
Often the production target is not achieved at PT. Satria Alam Manunggal is a problem that often occurs, this certainly disrupts the company's work cycle. For the planned Overburden Production Target at PT. Satria Alam Manunggal in June 2023 is 287,276 bcm while for coal it is 45,665 tons. However, in research carried out in that month, overburden and coal production was not achieved due to several factors, including the influence of rain, narrow fronts, and also the compatibility factor of loading and digging equipment with transport equipment. From the results of research conducted in June 2023 at PT. Satria Alam Manunggal obtained a tool compatibility calculation result of <1, meaning that the excavator loading tool only worked less than 100%, causing waiting time for the excavator loading tool, in this case it was one of the factors that caused production to not be achieved. In order to overcome these problems, the Company must make efforts to optimize the performance of mechanical equipment. By optimizing these mechanical tools, it is hoped that mining activities can be more optimal so that production can be achieved both in overburden stripping and coal production.